Potret Laki-laki dalam novel Rijal fi Asy-Syams Karya Ghassan Kanafani: Analisis Linguistik korpus: Gender Representation in Ghassan Kanafani’s Rijāl fī al-Syams - Ilmi, Kurnia Amalia; Sutaman; Penny Respati Yurisa (Jurnal Internasional Pendidikan Bahasa Arab, 2025)
Although Rijāl fī al-Syams by Ghassan Kanafani is recognized as a key work in Palestinian resistance literature, most previous studies have focused on its political themes and historical symbolism, with little attention to the linguistic construction of masculinity. As gender is a dynamic concept shaped by cultural and social contexts, examining male identity representation in literary texts is vital for understanding power relations, identity, and social roles. This study investigates masculinity in Rijāl fī al-Syams using a corpus linguistic approach, identifying patterns that portray male characters in terms of social roles, emotional expressions, ethical positioning, and comparing findings with Janet Saltzman Chafetz’s theory of masculinity. A mixed-method design combines with corpus analysis using Sketch Engine to examine word frequency, collocation, and concordance. Data analysis involves identification, classification, interpretation, and conclusion. The results reveal nine high-frequency words positioning male characters as central figures, leaders, and father figures, along with twelve attributive phrases and four verbal phrases reflecting social, ethical, physical, and emotional dimensions. The findings highlight an alternative, more inclusive, humanized form of masculinity, aligning with Chafetz’s critique of hegemonic masculinity. This study demonstrates the value of corpus linguistics in Arabic literary research, offering an objective method for analyzing gender representation